Sex-based differences in lung cancer susceptibility and molecular genetics in the 2020s - Berta Mosleh; Pavla Sarova; Sonja Zehetmayer; Felicitas Oberndorfer; Joachim Widder; Helmut Prosch; Marco Idzko; Clemens Aigner; Mir Alireza Hoda; Daniela Gompelmann (Heliyon)
Introduction: Sex-based differences in histological subtypes, in frequencies of mutations, and differences in response to the various therapeutic approaches in lung cancer are well studied. In general, the literature is controversial, and the large majority of the investigations may not provide evidence from the last decade. Objective: The objective of the current study was to reveal timely sex-based differences in patients with lung cancer in the era of immunotherapy and molecularly targeted agents. Methods: We retrospectively analyzed a consecutive cohort of 286 patients (female:male ratio 134:152/47 %:53 %) who were diagnosed with lung cancer between 2020 and 2022 in the pulmonology department of the Medical University of Vienna, Austria. Demographic characteristics, histological subtypes, the PD-L1 expression on tumor cells, presence of mutations, treatment, and survival of male and female patients were compared. Results: The smoking rate in women with lung cancer was significantly lower than in men (p = 0.005). The rate of targetable mutations was significantly higher in female patients (52 % vs. 30 %, p = 0.011). There were no significant differences in age at diagnosis, body mass index, lung function parameters, histological subtypes, PD-L1 protein expression, disease stage, and survival between men and women (all p > 0.05). Conclusion: Female Caucasian patients seem to have a higher susceptibility to lung cancer. Although the rate of genetic alterations is similar in both sexes, actionable driver mutations are significantly more common in women.